Hubungan Fleksibilitas Otot Tungkai dengan Kasus Low Back Pain Ischialgia di Desa Adikarso Kebumen Jawa Tengah: (Uji Korelasi Sit and Rich Test dengan Oswestry Low Back Pain Disability Questionnaire) - Muhammad D. Kurniawan; Cahyo Setiawan; Laksmita Dewi Adzillina (Jurnal Kesehatan Amanah, 2024)
Low back pain (LBP) is a common health issue with a high prevalence in the population, including in rural areas. This study aims to explore the relationship between lower limb muscle flexibility, measured using the Sit and Reach Test (SART), and the level of disability due to LBP, assessed through the Oswestry Low Back Pain Disability Questionnaire (OLBPDQ), among 92 respondents in Adikarso Village, Kebumen. Pearson correlation analysis revealed a significant negative relationship between limited muscle flexibility and the level of disability due to LBP (p = 0.04). Respondents with low flexibility (<8 cm) tended to experience LBP with severe disability (41%-60%), while better flexibility (9-16 cm) was associated with moderate to minimal disability. These findings underscore the importance of muscle flexibility in the prevention and management of LBP and support a multidisciplinary approach that includes improving flexibility, physical activity, and lifestyle modifications to reduce the burden of LBP and enhance quality of life.